Respect, man - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Imagine that even big men in my village respect me whenever they see me with Spore. I bet they are wondering how I get my copy! anonymous, Nigeria1 [The World of Spore Readers (2:10)] [Summary report of the Uses of Spore Survey] [readers ...